2020
DOI: 10.1186/s12889-020-09576-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring commissioners’ willingness-to-pay for community based childhood obesity prevention programmes using a discrete choice experiment

Abstract: Background In the UK, rates of childhood obesity remain high. Community based programmes for child obesity prevention are available to be commissioned by local authorities. However, there is a lack of evidence regarding how programmes are commissioned and which attributes of programmes are valued most by commissioners. The aim of this study was to determine the factors that decision-makers prioritise when commissioning programmes that target childhood obesity prevention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Justification of this approach was considered at length by the team and in discussion with the independent steering committee. Given that commissioners value both enrolment and attendance [ 42 ], it was agreed that improvements in either would be deemed effective (and subsequent adjustment was made to the analysis to account for multiplicity).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Justification of this approach was considered at length by the team and in discussion with the independent steering committee. Given that commissioners value both enrolment and attendance [ 42 ], it was agreed that improvements in either would be deemed effective (and subsequent adjustment was made to the analysis to account for multiplicity).…”
Section: Methodsmentioning
confidence: 99%
“…However, subsequent null trial findings indicated that this was not appropriate. Instead, a discrete choice study [ 50 ] was conducted to consider, more widely, what delivery elements of obesity prevention programmes are most valued by commissioners [ 42 ]. The sample size within the published protocol did not allow for analysis of two primary endpoints and incorrectly included reference to a single composite endpoint.…”
Section: Methodsmentioning
confidence: 99%
“…However, subsequent null trial ndings indicated that this was not appropriate. Instead, a discrete choice study (39) was conducted to consider, more widely, what delivery elements of obesity prevention programmes are most valued by commissioners (40). The sample size within the published protocol did not allow for analysis of two primary endpoints and incorrectly included reference to a single composite endpoint.…”
Section: Changes To Methods After Trial Registrationmentioning
confidence: 99%
“…We used a discrete choice experiment (DCE) to understand public preferences towards different financial incentive attributes. The DCE has been used widely in health economics and the studies that examine preferences towards weight loss program attributes are especially relevant to this study [28][29][30]. The application of choice experiment allows us to examine a wider range of incentive attributes (i.e., more and broader ranges of levels within each attribute), overcoming the limitations of actual field experiments (i.e., limited scope, limited representativeness, and limited incentive designs).…”
Section: Experimental Methods and Implementationmentioning
confidence: 99%